A Profile of Sydney World Masters Games Athletes: Health, Injury and Psychological Indices - Joe Walsh; Ian Timothy Heazlewood; Mark DeBeliso; Mike Climstein (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
The World Masters Games (WMG) are an international, multi-sport event which, in terms of competitor numbers, is the world's largest. The purpose of this manuscript was to summarize research to date that has been conducted on the WMG cohort. This paper also reports a descriptive and analytical overview of this large sample to document aspects of demographics and health indices for this population. Masters athletes demonstrated significant improvements in health related indices over age matched comparative national populations. Notable among these improvements were body mass index and cardiovascular disease (CVD) risk factors for the majority of participants, with female WMG participants presenting improved scores for CVD risk factors (blood pressure and high density lipoproteins, p < 0.05) and body mass index (p < 0.05) when compared to males. There were also improved lifestyle behaviors such as reduced smoking. A concern was improved health indices might be negated by increased injury from competitive sport at older ages, however findings did not support the premise of masters football code athletes having higher incidence of injury compared to younger athletes. With improved health indices associated with masters competition, it is relevant when promoting physical activity at older ages that the most motivating factor behind participation was socialization with others.